Signalling Effect of Auditor Reputation and Lock-Up Period on Over-Subscription Ratio: Evidence from Malaysian Fixed-Price IPOs - Ali Albada; Othman Yong; Soo-Wah Low (International Journal of Business and Society, 2020)
This study investigates the signalling effect of auditor reputation and lock-up period on the subscription demand of investors in the Malaysian IPO market that uses the fixed-price method in pricing IPOs. The study sample covers 420 IPOs listedon Bursa Malaysia from January 2000 to December 2015. The present study employsOrdinary Least Square(OLS)andQuantile Regression(QR)methodsin investigating the signalling effect on over-subscription ratio (OSR). The results indicate that auditor reputation has a negative effect and the lock-up period has a positive effect on OSR. This shows that investors’ demand in Malaysia is driven by capital gain and not by the quality of the listing firm. This is also supported by the control variables, where IPOs with low initial return, high offer price, high institutional involvement, and reputable underwriterhave lower OSR because they have lower initial returns.